Finance and Development, December 1965. (Finance and Development; Finance and Development, 1965)
This paper highlights that the annual meetings of the World Bank and its affiliates, the International Development Association (IDA) and the International Finance Corporation (IFC), and of the IMF, were held in September 1965 in Washington. At the Bank Group meetings, stress was laid on the urgent needs of the less developed countries and on the Group's plans for increasing its help toward meeting these needs. In his annual address, the President of the three institutions, Mr. Woods, emphasized the widening spectrum of the World Bank's lending.